Assessing the Burden of Cesarean Deliveries in Diyala, Iraq: Incidence, Underlying Factors, and Health Implications for Mothers and Infants - Anfal Adnan Ahmed; Alyaa Aziz Ahmed; Sawsan Talib Salman (International Journal of Health and Medicine, 2025)
Aim of the study: The study aimed to investigate the causes, risk factors, and incidence of caesarean sections in Diyala province during the research period. Patients and Methods: This prospective study was conducted at Al-Batool Maternity Teaching Hospital between October 2023 and December 2023. The study population consisted of 96 women who attended the labor ward for delivery after 32 weeks of gestation, irrespective of the delivery method. Patients' data were collected using an organized questionnaire. The data were analyzed using the Chi-square test for independence between variables.  Results: Study outcomes revealed that the percentage of cesarean sections increased significantly with age, peaking among women aged 20-35 and those over 35 (67.1% and 77.8%, respectively), in contrast to the group under 20, where most deliveries were vaginal (81.8%). An increasing number of previous deliveries (four or more) led to a higher chance of cesarean sections in subsequent pregnancies (76.9% compared to 58.8%) for those with two to four previous deliveries versus those who were primipara (52.6%). The most common indication for elective cesarean sections among participants was a scarred uterus (62.5%), followed by fetal indications such as malposition, abnormal presentation, post-date, and oligohydramnios (15%). The leading reasons for unplanned cesarean sections included obstructed labor (30%), followed by cephalo-pelvic disproportion (20%), and maternal factors (15%). Conclusion: study finding highlight key risk factors influencing delivery methods, suggesting the need for tailored obstetric care to optimize birth outcomes and reduce unnecessary CS procedures.